Volunteering and place-belonging: the case of historical and environmental interest groups in the National Forest - Towns, Felicity (2014)
This thesis investigates volunteering and place-belonging amongst historical and environmental interest groups in The National Forest. With the main focus on the nature of environmental and local historical interest groups, the volunteers who are involved with these groups and their senses of belonging and relationships with place.